Rust Diseases of Willow and Poplar 2005
DOI: 10.1079/9780851999999.0131
|View full text |Cite
|
Sign up to set email alerts
|

Disease scoring by taking inoculum densities into consideration in leaf disc inoculations with poplar and willow rusts.

Abstract: This chapter discusses the relationships between inoculum density and uredinial number/area using the data obtained with poplar rust (Melampsora larici-populina) and willow rust (M. larici-epitea). A method for disease scoring in leaf disc inoculations using slope factors calculated based on the uredinial pustule area and inoculum density is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Recent study suggested that the number of spores applied can greatly influence the number of pustules produced in M. larici‐epitea (Pei et al ., 2002). In this study, disease was scored based on pustule area and inoculum density data according to the method described by Pei & Hunter (in press) using the following steps: (i) for each clone/isolate combination, a slope factor was calculated by dividing average square root pustule area per leaf disc by the square root of the inoculum density per leaf disc for the isolate; (ii) for each isolate, the clone which produced the largest pustule area (the most susceptible reaction) was chosen and the maximum slope factor was calculated by dividing its average square root of the pustule area by the square root of inoculum density (an average maximum slope factor, AMSF) was calculated by averaging the maximum slope factors for all the isolates); (iii) disease was scored for each clone/isolate combination using 0–4 scales. An assumption was made that the average maximum slope factor represents the midpoint for the scale 4, the most susceptible reaction.…”
Section: Methodsmentioning
confidence: 99%
“…Recent study suggested that the number of spores applied can greatly influence the number of pustules produced in M. larici‐epitea (Pei et al ., 2002). In this study, disease was scored based on pustule area and inoculum density data according to the method described by Pei & Hunter (in press) using the following steps: (i) for each clone/isolate combination, a slope factor was calculated by dividing average square root pustule area per leaf disc by the square root of the inoculum density per leaf disc for the isolate; (ii) for each isolate, the clone which produced the largest pustule area (the most susceptible reaction) was chosen and the maximum slope factor was calculated by dividing its average square root of the pustule area by the square root of inoculum density (an average maximum slope factor, AMSF) was calculated by averaging the maximum slope factors for all the isolates); (iii) disease was scored for each clone/isolate combination using 0–4 scales. An assumption was made that the average maximum slope factor represents the midpoint for the scale 4, the most susceptible reaction.…”
Section: Methodsmentioning
confidence: 99%
“…Also, in Melampsora rusts on willow and poplar, inoculum densities can greatly influence the number of pustules produced (Pei et al. , 2002, 2004b; Pei & Hunter, 2005). In the present study, direct measurement of uredinia provided objective and precise data and the weighting of the differences in inoculum density made it easier to compare the disease data between inoculations.…”
Section: Discussionmentioning
confidence: 99%
“…Disease severity was scored for each willow genotype by dividing the average square root of pustule area per leaf disc by the square root of inoculum density in each combination of willow family and rust isolate. This method of disease scoring was proposed previously (Pei & Hunter, 2005) based on the linear relationships between uredinial pustule area and inoculum density in the willow rust M. larici‐epitea and the poplar rust M. larici‐populina . A relative disease score (RDS) was calculated for each genotype by dividing its disease score by the highest disease score for that willow family/rust isolate combination.…”
Section: Methodsmentioning
confidence: 99%